PERANAN KERAPATAN ADAT NAGARI (KAN) DALAM PENYELESAIAN SENGKETA TANAH KAUM DI NAGARI KOTO ANAU KABUPATEN SOLOK PROPINSI SUMATERA BARAT - , Eko Syaiful; , Sulastriyono, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research focused to the role of Local Customary (LCI) in the resolution of land disputes to the village of Koto Anau people of Solok Regency in West Sumatera Province aims to determine how thw role of it in the settlement of land disputes among Koto Anauâs people of Solok Regency in West Sumatera Province and to identify the obstacles will be encountered in connection with the settlement of land disputes among them. In connection with the proposed research, the approach of method used in empirical research was juridical. The technique of data collection in this research was field research associated with the rules of law and provided by library research. It used directly communication technique by instrument in the form of unstructured interview guide (unstructured interview). The data were analyzed qualitatively and descriptively. Based on research has been conducted can be concluded that before the settlement to the land disputes enter to the authority of Local Costumary Institude (LCI) of Koto Anau, the dispute was settled first by the elders at the head of the heirs and if in this level can not be resolved then proceed come to Tribe Chief. This level was called âBajanjang Naiak, Batanggo Turunâ , (up by stair and down by stair). The term was used in Koto Anau Village to all dispute resolution. The Local Costumary Institute (LCI) in running itâs role in accordance with to Local Rule No.2 in 2007 on the main points of local goverment that was seeking peace and giving force to members of a village community who involved in the dispute and giving legal force o other evidence according to the prevailing custom. The obstacles in the form of land dispute resolution for example difficulty of presenting the parties involved with the dispute resolution for example difficulty of presenting the witness, difficulties in issuing the decision by LCI such as the existence of the disputed objects was obscure.